2019
DOI: 10.29333/iji.2019.12443a
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Educational Infographic on Students’ Interaction and Perception in Jordanian Higher Education: Experimental Study

Abstract: This study aims to evaluate the effect of employing infographics in higher education, specifically with regard to students' interactions and their perception of the meaning of transferred information. This evaluation was presented through lectures at Applied Sciences Private University in Jordan and two other selected colleges (one scientific and the other humanistic) to compare the two variables applied in this study. To achieve this object infographic materials were developed by researcher and guided by (ASS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 18 publications
1
27
0
1
Order By: Relevance
“…So that infographics are developed in visual media for teaching English that follows the principles of a good visual media (Reyna, 2016). Infographic is a visual media that are used to convey information in a brief and brief manner (Alqudah et al, 2019). As a teaching medium, infographics will also be developed in a summary and concise manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So that infographics are developed in visual media for teaching English that follows the principles of a good visual media (Reyna, 2016). Infographic is a visual media that are used to convey information in a brief and brief manner (Alqudah et al, 2019). As a teaching medium, infographics will also be developed in a summary and concise manner.…”
Section: Discussionmentioning
confidence: 99%
“…The infographic has a simple appearance that includes only one slide. Therefore, the presentation of the material will be summarized briefly and clearly in one slide (Alqudah et al, 2019). Thus, teachers and students will facilitate their teaching and learning process through the use of infographics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The students preferred to study with visual materials rather than the traditional materials such as books. Another similar research was conducted by Alqudah et al (2019) that has a purpose to investigate the impact of using educational infographic by focusing on the students' interaction and perception of the meaning of the transferred information. The results of this study showed that infographic had positive effect on both college's samples and it has been proved by comparing the students' quizzes scores between the control group and experimental group.…”
Section: Introductionmentioning
confidence: 99%
“…Infographic is one of the visual communication form which has the capability to express the expected meaning of information visually. Thus it is also help the student to identify the information by the carrier of information (Alqudah, 2019).…”
Section: Introductionmentioning
confidence: 99%